2017
DOI: 10.18203/2320-6012.ijrms20171856
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and socio-economic class

Abstract: Background: Childhood obesity has reached epidemic levels in developed countries. Overweight and obesity in childhood are known to have significant impact on both physical and psychological health. The mechanism of obesity development is not fully understood and it is believed to be a disorder with multiple causes. There are supporting evidence that excessive sugar intake by soft drink, increased portion size and steady decline in physical activity have been playing major role in the rising rates of obesity al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The point of inflection at oxidation curve is called the induction period (IP) or oxidative stability index (OSI). The end of the induction period was characterized with rapid increase in solution conductivity that was caused by dissociation of volatile organic acids produced in the oxidation process and their absorption in deionized water [22,27,37].…”
Section: Methodsmentioning
confidence: 99%
“…The point of inflection at oxidation curve is called the induction period (IP) or oxidative stability index (OSI). The end of the induction period was characterized with rapid increase in solution conductivity that was caused by dissociation of volatile organic acids produced in the oxidation process and their absorption in deionized water [22,27,37].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, as these actuators are compatible with traditional electronic devices, they can be easily integrated with energy devices and electric drivers. The range of applications is unlimited; some of the greatest research fields are found in artificial muscles, [33][34][35] microrobots, [36,37] microscale object manipulation, [38] and microfluidic systems. [39][40][41] In the following, we will discuss the two specific types of electrically responsive actuators that have been widely used-dielectric elastomers and servomotor-based mechanical actuators.…”
Section: Overview Of Methods For Soft Actuators 21 Electrically Resmentioning
confidence: 99%